ULTRASOUND-ASSISTED SYNTHESIS OF NOVEL 3-(PYRIDINYLAMINO)-1-FERROCENYLPROPAN-1-ONES - Minić Jančić, Aleksandra; Ilić Komatina, Danijela; Todosijević, Anka; Stevanović, Dragana (Bulletin of Natural Sciences Research, 2021)
In this work we will report the formulation of novel 3-(pyridinylamino)-1-ferrocenylpropan-1-ones. A fruitful aza-Michael addition of pyridinamine moiety to a conjugated enone, 1-ferrocenylpropenone, has been accomplished by an ultrasonic irradiation of the mixture of these reactants. As the catalyst montmorillonite K-10 has been used and the reaction has been carried out as solvent-free, yielding ferrocene containing Mannich bases, compounds considered as important precursors in organic synthesis. The reaction score has been evaluated on three examples. The prepared products have been purified by column chromatography. In addition, a detailed characterization of the obtained 3-(pyridin-2-ylamino)-1-ferrocenylpropan-1-on and 3-(pyridin-3-ylamino)-1-ferrocenylpropan-1-on has been completed by IR and NMR spectroscopy, as well as elemental analyses.
Keywords: aza-Michael addition; Ultrasound irradiation; 3-(pyridinylamino)-1-ferrocenylpropan-ones; Mannich bases; Spectral characterization